Education as a means to minimize expressions of discrimination and exclusion - Nilsa Shirley Benítez (Senderos Pedagogicos, 2013)
This study intends to ratify education as a tool to empower skills, interests and abilities among people. Also it sees education as a means to mobilize attitudes that allow advancing in the formation of less discriminatory and exclusionist societies, where diversity, as a human condition and being’s essence, is acknowledged, respected and valued. The point of departure is an approach to the terms of diversity and discrimination, as the latter emerges from interaction with the context in cases where the other is forced, minimized or rejected for the sole fact of being different, and not to fit in some established social canons. Finally, it reflects on education as a tool that allows moving from discrimination and exclusion to respect, acceptance and acknowledgement of difference.